Genetic characteristics of Nenets reindeer depending on their gender - Nikolaev S.V.; Matyukov V.S; Filatov A.V. (Ветеринария и кормление)
The aim of the work was a comparative assessment of the genetic diversity of Nenets reindeer depending on their gender. The object of research was animals of the Nenets breed of the Yamal experimental station of the Tyumen Scientific Research Center SB RAS (Salekhard). A total of 49 samples of auricle tissues obtained from males and 253 samples from females were subjected to DNA analysis. It was found that there are 24 microsatellites among the important ones, which are absent from the choirs. Private alleles were identified for all 9 analyzed loci, the average frequency of which was 0.073. A half-focus analysis of the correspondence of the observed and expected genotypes showed that the greatest similarity, regardless of gender, was observed at the NVHRT24 locus, and the maximum discrepancy was seen in RT6 in choirs, and RT30 in vazhenok. A significant discrepancy in the prevalence of observed and expected genotypes in males was typical for NVHRT76, RT27 and NV21 (PЈ0.001), and in females for all 9 analyzed loci (PЈ0.05...0.001). The analysis of the main genetic parameters indicates that the average number of observed microsatellite variants among the vazhenki was 2.24 more (PЈ0.05) compared with the choruses. The greatest discrepancy between the observed and effective microsatellites in males was characterized by the RT30 locus (a difference of 3.88 times), in females - RT9 (a difference of 3.75 times). A polocus analysis of the level of inbredity showed that the greatest correspondence between the observed and expected heterozygosity in choirs is characterized by the RT9 locus (-0.017), and RT6 locus (-0.020) in females. A noticeable deficiency of heterozygosity, regardless of gender, was observed in NV21 (choruses - 0.693; vazhenki - 0.511), whereas a pronounced shift towards an excess of heterozygotes was observed only among males at the RT6 locus (-0.272). The RT6 locus (DN=0.006) was characterized by the closest possible structure between the vazhenki and choruses, and the RT9 loci (DN=0.152) and RT30 (DN=0.299) had the greatest genetic difference. However, the average genetic divergence between males and females was not significant (DN=0.073). The data obtained predict a further narrowing of the genetic diversity of the analyzed population in the absence of choral exchange.